MARE-WINT New Materials and Reliability in Offshore Wind Turbine Technology - Ostachowicz, Wiesław; McGugan, Malcolm; Schröder-Hinrichs, Jens-Uwe; Luczak, Marcin (Springer International Publishing : Imprint: Springer, 2016)
This book provides a holistic, interdisciplinary overview of offshore wind energy, and is a must-read for advanced researchers. Topics, from the design and analysis of future turbines, to the decommissioning of wind farms, are covered. The scope of the work ranges from analytical, numerical and experimental advancements in structural and fluid mechanics, to novel developments in risk, safety & reliability engineering for offshore wind.  The core objective of the current work is to make offshore wind energy more competitive, by improving the reliability, and operations and maintenance (O&M) strategies of wind turbines. The research was carried out under the auspices of the EU-funded project, MARE-WINT. The work seeks to bridge the gap between research and a rapidly-evolving industry. .